PENGARUH CORPORATE GOVERNANCE PADA NILAI PERUSAHAAN - Muryati, Ni Nyoman Tri Sariri; Suardikha, I Made Sadha (E-Jurnal Akuntansi; Vol 9 No 2 (2014), 2014)
The purpose of this study was to examine the influence corporate governance on firm value. Proxy of corporate governance is internal mechanisms (managerial ownership, independent commissioners, board of directors, and independent audit committee) and external mechanisms (institutional ownership). The samples were banking companies listed on the Indonesia Stock Exchange in 2009-2012. Purposive sampling method used in the selection of the sample so that the obtained  sample of 20 banking companies with total of observations is 80 observation data during 4 years. There are 5 data outliers were excluded from the analysis in order to obtain as many as 75 observations. Data analysis techniques using multiple regression analysis. Firm value is measured using Tobin's Q. Based on the results of testing the hypothesis, obtained results that only the independent audit committee variables that negatively affect on firm value while the other four independent variables has a positive effect on firm value.
Keywords: corporate governance, internal mechanisms, external mechanisms, and firm value